Pengaruh Lifestyle dan Price Terhadap Buying Intention Produk Smartphone Samsung pada Pelajar di Kota Sukabumi. - Umban Adi Jaya; Widia Sriningsih (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2018)
The purpose of this study is to determine the influence of lifestyle dimensions or variables on buying intention of Samsung Smartphone brand products. The research method uses quantitative methods by using primary that is taken from questionnaires and distributed to 100 respondents by stratified random sampling technique to senior high school students in Sukabumi City. Instrument testing techniques use validity and reliability testing. Data analysis techniques used descriptive and correlation analysis while for testing hypotheses using multiple regression analysis. In this study it can be concluded that lifestyle has a significant effect on buying intention with a value of t count 5,000 and t table 1,984 or 5,000> 1,984 as well as the price has a significant effect on buying intention with t count value 5.570 and t table 1.984 or 5.570> 1.984. Simultaneous results show lifestyle and price affect the buying intention with the results of table f 59.8882 and 3.940 or 59.8882> 3.940.